2016
DOI: 10.4172/2161-0940.1000248
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Analysis and Acute Toxicological Study of Erythrina senegalensis Ethanolic Leaf Extract in Albino Wistar Rats

Abstract: Objective: Erythrina senegalensis is used to cure wide range of illnesses such as malaria, gastrointestinal disorders, fever, dizziness, asthma. Given its widespread usage, the study sought to investigate the phytochemical analysis and acute oral toxicity (LD50) of E. senegalensis. Materials and methods:Fresh mature leaf samples of E. senegalensis were collected and phytochemical analysis was carried out appropriately. The acute toxicity study of the leaf extract was determined using modified Lorke's method. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
0
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 9 publications
1
0
0
Order By: Relevance
“…Flavonoids and phenols were present in high quantities while glycosides were not detected. This is consistent with the report of Nnama et al (2017), and Osuntokun et al (2016), who reported that the leaf extract of E. senegalensis contains phytochemicals such as saponins, flavonoids, tannins, terpenoids, glycosides and alkaloids. Alkaloids have been shown to have many pharmacological activities including; antihypertensive effects (indole alkaloid), antiarrhythmic effect, antimalarial activity (quinine), anticancer activity (Togola et al 2008;Mamta et al 2013) and wound healing property (Ilodigwe 2014).…”
Section: Discussionsupporting
confidence: 92%
“…Flavonoids and phenols were present in high quantities while glycosides were not detected. This is consistent with the report of Nnama et al (2017), and Osuntokun et al (2016), who reported that the leaf extract of E. senegalensis contains phytochemicals such as saponins, flavonoids, tannins, terpenoids, glycosides and alkaloids. Alkaloids have been shown to have many pharmacological activities including; antihypertensive effects (indole alkaloid), antiarrhythmic effect, antimalarial activity (quinine), anticancer activity (Togola et al 2008;Mamta et al 2013) and wound healing property (Ilodigwe 2014).…”
Section: Discussionsupporting
confidence: 92%
“…The phytoconstituents like alkaloids and glycosides in leaf extract of E. variegata were found to be in more concentration in butanol followed by chloroform extract and whereas the other phytoconstituents like flavonoids and phenols were found to be more in butanolic extract (Figure 1 and Table 7). Similarly phytochemical analysis of the ethanolic leaf extract of E. senegalensis showed the presence of alkaloids, saponins and flavonoids in moderate quantities [NNAMA & al. 2017].…”
Section: Phytochemical Screening Leaf Extractmentioning
confidence: 99%
“…El consumo de forraje fresco de pisonay después de 21 días, en proporciones por encima del 50% originarían la presencia de anomalías en el hígado e incrementaron las enzimas alanina (61.9 UI/L) y aspartato (76.3 UI/L) aminotransferasas, por la presencia de taninos y alcaloides en las hojas, indicaría probable toxicidad (6), en otros estudios, se ha observado que en las hojas de Erythrina senegalensis mostraron la presencia de saponinas y flavonoides, además de terpenoides, que no causarían toxicidad aguda en roedores (7), por otro lado, el extracto de Erythrina variegata en ratas Wistar, provocaron cambios leves en la proteína total, albumina, bilirrubina total y aspartato aminotransferasa sin alejarse de los rangos normales, a excepción de los niveles de alanina aminotransferasa, estas variaciones indicarían que el daño fue reversible a nivel hepático y no causaría toxicidad subcronica (8).…”
Section: Introductionunclassified